Germination responses of three congeneric cactus species (Neobuxbaumia)with differing degrees of rarity. - Ramírez-Padilla, C.A.; Valverde, T.
Seed germination patterns may have a direct impact on the level of rarity of a species. We analysed the germination behaviour of three cactus species differing in their degree of rarity: Neobuxbaumia macrocephala, N. tetetzo, and N. mezcalaensis. Germination treatments included different temperatures, immersion in HCl, darkness, and different water potentials. The rarest species, N. macrocephala, showed the lowest germinability compared to the other two species; N. mezcalaensis (the most common)showed a photoblastic response and was considerably affected by water potential. These results are discussed in terms of the differences in the level of rarity between the three species.
Keywords: ECOPHISIOLOGY; GERMINATION; SEED ECOLOGY; ARID ENVIRONMENTS; EARLY ESTABLISHMENT; PLANT CONSERVATION; RARITY